The effectiveness analysis of direct marketing strategies at PT. Bathi Dua Putra, Balikpapan City - Lugas Bati Supriadi; Nur Laili Fikriah (Jurnal Mantik, 2023)
This research aims to analyze the effectiveness of direct marketing strategies at PT. Bathi Dua Putra Balikpapan City. This research was carried out at PT Bathi Dua Putra. The marketing strategy used by BDP Cargo to achieve business success is by using a direct marketing strategy. The subjects in this research involved Company Employees (Description) consisting of directors, procurement department employees, operational employees, marketing employees, financial employees, consumers of PT Bathi Dua Putra. The types of data in this research are primary data and secondary data. Direct marketing strategies at BDP Cargo are effective in increasing the number of consumers and sales. This is also because BDP Cargo is able to understand consumer needs, which is demonstrated by fast delivery with same day service, and neat work. BDP Cargo constraints are divided into two sources, namely internal and external constraints